Association between the lunar cycle and pregnancy at first artificial insemination of Holstein cows - P. Pinedo; K. Keller; M. Schatte; J. Velez; T. Grandin (JDS Communications)
The objective of this observational study was to analyze the association of the lunar cycle with pregnancy at first artificial insemination (P/AI1) of Holstein cows. The study cows were managed under organic certification, which prohibits the use of exogenous hormones for synchronization of ovulation and requires continuous access to open dry lots. Two categorizations of the lunar cycle were used for the analysis: lunar phases 4 (LP4) with 4 categories of equal duration (new moon to first quarter, first quarter to full moon, full moon to third quarter; and third quarter to new moon) and lunar phases 8 (LP8) with 8 categories (new moon, first quarter, full moon, third quarter [set to 1 d duration each] and waxing crescent, waxing gibbous, waning gibbous, and waning crescent [4 d of duration each]). Two sets of data were created where first postpartum inseminations were matched with the corresponding lunar phase for the 2 categorizations (LP4 and LP8) using the artificial insemination (AI) dates. Data were examined separately in primiparous and multiparous cows. Least squares means for P/AI1 by lunar phase were calculated and compared using ANOVA. Potential associations between P/AI1 and the 2 lunar phase categorizations were initially tested by chi-squared test of independence followed by multivariable logistic regression. Differences in P/AI1 LSM were established only in primiparous cows in the LP8 categorization. Cows receiving AI1 during the first quarter had a smaller probability of P/AI1 (0.29) as compared with waxing gibbous (0.39), waning crescent (0.40), waning gibbous (0.42), and third quarter (0.46). The logistic regression analyses were completed using the new moon category as reference. The analysis identified greater odds of P/AI1 during the third quarter than during the new moon in both primiparous (odds ratio [95% CI] = 1.15 [1.02–1.30]) and multiparous (1.12 [1.01–1.24]) cows. When LP8 was considered for the logistic regression analysis, associations between the lunar cycle and P/AI1 were only identified in primiparous cows for the first quarter compared with the new moon (odds ratio [95% CI] = 0.67 [0.47–0.94]). In conclusion, this study identified small associations between the lunar cycle and pregnancy at first insemination of Holstein cows maintained in an organic-certified herd. Validating the associations described here and clarifying the biological basis of the reported differences in P/AI1 would require controlled studies in other cattle populations.